Cultural and Historical Roots of Performance Art - Mukhametzyanov, Rustem; Martynova, Yulia; Martynov, Dmitry; Mingalieva, Leysan (Journal of History Culture and Art Research, 2018)
The 20th century is marked by colossal progress not only in science and technology, but also in art. Since the first half of 20th century there has been a gap observed between traditional and modern art. Modern art includes a variety of forums, biennale, museums of contemporary art, art space, etc. To date, performance is called all sorts of shows taking part in front of viewers. This can include the newfangled music shows, and various installations in museums, DJs sets in clubs and music festivals. Today, this art does not lag behind the rapidly developing communication industry, and at the same time resists the impact of technologies that help to distance people from each other. Performance, in spite of insufficient knowledge, is a popular type of contemporary art. Thus, the performance is introduced into the modern society, leaving behind itself food for reflection. The paper is of interest to researchers of contemporary art and the evolution of cultural phenomena in the 20th century. The work is based on a combination of historical methods, including historical-genetic and historical-comparative.